La multifuncionalidad y el multipropósito de la oralidad y el modelo de gestión para su desarrollo en el proceso civil peruano - Guerra Cerrón, María Elena (2022)
The system and specifically the oral model in the civil process is based on the judicial guarantees that constitute human rights and its characteristics are multifunctionality and multipurpose, thus it is adequate for the realization of rights. In Peru since 2019, a management model has been implemented for the development of the civil process that is based on: the planning, direction and organization of the judicial office and the ordering of cases.